2Cos(3x)-x+24=

Simple and best practice solution for 2Cos(3x)-x+24= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2Cos(3x)-x+24= equation:


Simplifying
2Cos(3x) + -1x + 24 = 0

Remove parenthesis around (3x)
2osC * 3x + -1x + 24 = 0

Reorder the terms for easier multiplication:
2 * 3osC * x + -1x + 24 = 0

Multiply 2 * 3
6osC * x + -1x + 24 = 0

Multiply osC * x
6osxC + -1x + 24 = 0

Reorder the terms:
24 + 6osxC + -1x = 0

Solving
24 + 6osxC + -1x = 0

Solving for variable 'o'.

Move all terms containing o to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + 6osxC + -24 + -1x = 0 + -24

Reorder the terms:
24 + -24 + 6osxC + -1x = 0 + -24

Combine like terms: 24 + -24 = 0
0 + 6osxC + -1x = 0 + -24
6osxC + -1x = 0 + -24

Combine like terms: 0 + -24 = -24
6osxC + -1x = -24

Add 'x' to each side of the equation.
6osxC + -1x + x = -24 + x

Combine like terms: -1x + x = 0
6osxC + 0 = -24 + x
6osxC = -24 + x

Divide each side by '6sxC'.
o = -4s-1x-1C-1 + 0.1666666667s-1C-1

Simplifying
o = -4s-1x-1C-1 + 0.1666666667s-1C-1

Reorder the terms:
o = 0.1666666667s-1C-1 + -4s-1x-1C-1

See similar equations:

| 2p=-n | | 2y+12=-10x | | N/3=6.6 | | 12x-3=36+3 | | 11a-4a=Xa | | (3x+2)(x-4)-(3x+2)(x+8)=0 | | p+2n=0 | | 10b-2= | | 30=3n+1p | | 16=4y-12 | | 2x(3x-5)x=4 | | 6x+-6= | | 3÷5/3 | | 20=3n+1p | | 6x+-15= | | 6t-t+6= | | 2(x-8)-7x=-6 | | 2x(3x-5)forx=4 | | 10y-15+8y+2+6y+11=180 | | 5.825= | | N/m=8 | | 2x^3-19x^2+34x+22=0 | | 222=5z+4z+3 | | 5p-3+p= | | 3(7-2f)=31 | | 2(4)+y=-4 | | 4x^2y^5-8xy^3=0 | | 5[x+(x+1)]-10= | | 294-3.50/12=X | | 2(2)+y=-4 | | 50/1.45 | | (3x+1)+(x+23)=180 |

Equations solver categories